Disruption of the Suprachiasmatic Nucleus in Fibroblast Growth Factor Signaling-Deficient Mice - Miller, Ann V.; Kavanaugh, Scott I.; Tsai, Pei-San (Frontiers in Endocrinology, 2016)
Fibroblast growth factor (Fgf) 8 is essential for the development of multiple brain regions. Previous studies from our laboratory showed that reduced Fgf8 signaling led to the developmental alterations of neuroendocrine nuclei that originated within the diencephalon, including the paraventricular (PVN) and supraoptic (SON) nuclei. To further understand the role of Fgf8 in the development of other hypothalamic nuclei, we examined if Fgf8 and its cognate receptor, Fgfr1, also impact the integrity of the suprachiasmatic nuclei (SCN). The SCN control an organism’s circadian rhythm and contain vasoactive intestinal peptide (VIP)-producing neurons as the main input neurons. Mice hypomorphic for Fgf8, Fgfr1, or both were examined for their SCN volume and the number of VIP neurons on postnatal day (PN) 0; adult hypomorphic mice were further examined for SCN function by quantifying SCN neuronal activation using cFos as a marker. On PN0, mice homozygous for Fgf8 hypomorphy displayed the most severe reduction of the SCN volume and VIP neurons. Those heterozygous for Fgf8 hypomorphy alone or Fgf8 combined with Fgfr1 hypomorphy, called double heterozygotes (DH), showed normal SCN volume but significantly reduced VIP neurons, albeit less severely than the homozygotes. Adult wild type, heterozygous Fgf8 hypomorphs (F8 Het), and DH mice were also examined for SCN cFos activation at three time points: 1 h (morning), 6 h (afternoon), and 11 h (evening) after light onset. In F8 Het mice, a significant change in the pattern of cFos immunostaining that may reflect delayed morning SCN activation was observed. Overall, our studies provide evidence supporting that deficiencies in Fgf8 not only impact the structural integrity of the SCN but also the pattern of SCN activation in response to light.